Nanofat functionalized injectable super-lubricating microfluidic microspheres for treatment of osteoarthritis. (June 2022) - Han, Zeyu; Bai, Lang; Zhou, Jing; Qian, Yinhua; Tang, Yunkai; Han, Qibin; Zhang, Xiaoyu; Zhang, Mingzhu; Yang, Xing; Cui, Wenguo; Hao, Yuefeng
Abstract: Nanofat (NF) is a fine emulsion that has been used to treat a variety of diseases given its abundance of bioactive components. However, the biological functions of NF have been limited due to its inability to localize during implantation. In this study, NF was immobilized in microfluidic-generated aldehyde-modified polylactic glycolic acid (PLGA) porous microspheres (PMs) via Schiff base condensation and non-covalent binding in a three-dimensional (3D) porous network (PMs@NF). The PMs effectively enhanced the cartilage-targeted retention efficiency of NF, which also resulted in remarkable lubrication performance, with the friction coefficient being reduced by ∼80%, which was maintained over time. Meanwhile, the 3D penetrating structure of the microspheres stimulated cytokine secretion by the NF-derived stem cells, upregulating the expression of anabolism-related genes and downregulating catabolism, and the expression of inflammation-related and pain-related genes. Injecting PMs@NF into the knee joint cavity of a rat model with destabilization of the medial meniscus (DMM) reduced osteophyte formation and protected the cartilage from degeneration, thereby inhibiting the progression of osteoarthritis and improving animal behavior. In summary, this study developed a multifunctional platform with NF immobilization and super-lubrication, which showed great potential for the minimally invasive treatment of osteoarthritis.